METHODOLOGY OF COST CENTER MANAGEMENT CONTROL (THE CASE OF A PRECAST CONCRETE PLANT) - I. N. Chernykh (Российский технологический журнал)
The article deals with organizational aspects of management control of the cost centres on the example of a plant for the production of concrete products. In the study reviewed the organizational support of the system of management control by cost centers: the purpose of monitoring, the main objectives and elements of control (control environment, accounting system, control procedures). Presents information base, a list of objects and subjects of management control by cost centers in the organization under study: depending on role in the monitoring process, the level of detail of the responsibilities and range of contacts. In addition to the selection of subjects of management control by cost centers in the work outlines the main principles of management control of the cost centres and the possibility of their use in these parts of the organization. The conduct of preliminary, current and subsequent control by cost centers has a positive impact on the formation of the economic impact, constituting one of the main purposes of the system of internal management control in the organization. The author offers the scheme of the integrated management control of the cost centers of the plant for production of concrete products. Analyzed software management management accounting and control by cost centers in the organization.